Induksi Tunas dari Eksplan Kotiledon dan Epikotil In Vitro Jeruk Siam (Citrus nobilis Lour.) Asal Kampar pada Media MS - CAHYATI, SRI; ISDA, MAYTA NOVALIZA; LESTARI, WAHYU (Jurusan Biologi FMIPA Universitas Riau, 2016)
Citrus nobilis Lour. (Siam Orange) from Kampar is one of the main fruits in Riau Province that is highlyconsumed by many people, but nowadays its productivity is lower due to pests and diseases. In order tomaintain the availibility of citrus from Kampar and to conserve this plant, an effort that can be done is byusing in vitro culture with the use of a combination of growth regulator; cytokine and auxin usingcotyledons and epicotyl explant. This study aimed to determine the best explant source and to know theeffect of the concentration combination of BAP, kinetin, and NAA that optimal in inducing plant shoot ofSiam orange. This study was conducted at Laboratory of Integrated Biology, Department of Biology,Faculty of Mathematics and Natural Sciences using a completely randomized design (CRD) with variousconcentrations of treatments, and observed for 42 days. The results showed that the percentage of lifeexplants, swelling cotyledon, and epicotyl explants was 100%, the percentage of best shoot formation was60% on the epicotyls explant with 1.0 mg/l BAP + 0.5 mg/l kinetin + 0.5 mg/l NAA. The percentage ofcallus formation only found in epicotyls explants with the highest percentage (100%) at 2.0 mg/l BAP +0.5 mg/l kinetin +1.0 mg/l NAA.Keywords: Citrus nobilis Lour., cotyledons, epikotil, in vitro, shoot induction.